Ethics of human development according to the perspective of the Martha Nussbaum’s capabilities - Gómez Navarro, Ángel (2013)
This document analyzes the concept of human development from the perspective of the capabilities proposed by the American philosopher Martha Nussbaum. Be part of the need to take a new  perspective based on the person as an end in itself and an alternative to the perspective based on quantitative indicators. Thus, analyzing the 10th human development capabilities considering their respective effective end anthropological framework which support them. Taking a stand on the perspective criticism and concluding with a reflection on education as capabilities key.